Interregional electro-mechanical heterogeneity in the rabbit myocardium. (November 2017) - Dressler, Franz F.; Bodi, Ilona; Menza, Marius; Moss, Robin; Bugger, Heiko; Bode, Christoph; Behrends, Jan C.; Seemann, Gunnar; Odening, Katja E.
Abstract: Background: Increased electrical heterogeneity has been causatively linked to arrhythmic disorders, yet the knowledge about physiological heterogeneity remains incomplete. This study investigates regional electro-mechanical heterogeneities in rabbits, one of the key animal models for arrhythmic disorders. Methods and findings: 7 wild-type rabbits were examined by phase-contrast magnetic resonance imaging in vivo to assess cardiac wall movement velocities. Using a novel data-processing algorithm regional contraction-like profiles were calculated. Contraction started earlier and was longer in left ventricular (LV) apex than base. Patch clamp recordings showed longer action potentials (AP) in LV apex compared to the base of LV, septum, and right ventricle. Western blots of cardiac ion channels and calcium handling proteins showed lower expression of Cav1.2, KvLQT1, Kv1.4, NCX and Phospholamban in LV apex vs. base. A single-cell in silico model integrating the quantitative regional differences in ion channels reproduced a longer contraction and longer AP in apex vs. base. Conclusions: Apico-basal electro-mechanical heterogeneity is physiologically present in the healthy rabbit heart. An apico-basal electro-mechanical gradient exists with longer APD and contraction duration in the apex and associated regionally heterogeneous expression of five key proteins. This pattern of apical mechanical dominance probably serves to increase pumping efficiency.